Inocybe subhimalayanensis (Agaricales, Inocybaceae), a new smooth spored Inocybe species from Pakistan - Razzaq, Annum; Naseer, Arooj; Khalid, Abdul Nasir (European Journal of Taxonomy, 2023)
During mycological explorations, a new smooth spored species, Inocybe subhimalayanensis Razzaq, Naseer & Khalid sp. nov. was collected from moist temperate sub-Himalayan region, Pakistan. Phylogeny of ITS and LSU regions of nrDNA, and morphoanatomical data make it distinct from other known species of the genus. The taxon is characterized by: a yellowish orange to brown pileus with prominent fibrillose, prominent umbo; ellipsoid to amygdaliform smooth larger basidiospores (8.4‒)8.6‒12.2(‒12.6) × (4.9‒)5.1‒7.1(‒7.3) µm; and lack of velipellis. Molecular phylogenetic analyses further support the recognition of the new species.